Following Djuna women lovers and the erotics of loss - Allen, Carolyn (Indiana University Press, 1996)
" À la suite de Djuna est une analyse fascinante de l'érotisme textuel et des séductions lyriques de l'œuvre de Djuna Barnes et des écrivain.e.s qu'elle influence. Cette généalogie scintillante de l'intertextualité lesbienne. . . élargit le champ de la recherche littéraire lesbienne et féministe et les concepts de la production littéraire lesbienne. » —Judith Roof
Keywords: 1900-1999; arts; corps; discipline; personnes lesbiennes; périodes historiques; sexualité; thématiques; études littéraires

An intimate distance: women, artists and the body - Betterton, Rosemary.. (Routledge, 1996)
How have women artists taken possession of the female body? What is the relationship between looking and embodiment in art made by women? In a series of original readings of the work of artists from Kathe Kollwitz and Georgia O'Keeffe to Helen Chadwick and Laura Godfrey-Isaacs, Rosemary Betterton explores how women artists have addressed the changing relationship between women, the body and its representation in art. In detailed critical essays that range from the analysis of maternal imagery in the work of German artists at the turn of the century to the unrepresented body in contemporary abstract painting, Betterton argues that women's art practices offer new ways of engaging with our fascinations with and fears about the female body. Reflecting the shift within feminist art over the last decade, An Intimate Distance sets the reinscription of the body within women's art practice in the context of current debates on the body, including reproductive science, maternal subjectivity and the concept of 'body horror' in relation to food, ageing and sex. Drawing on recent theories of embodiment developed within feminist philosophy and psychoanalytic theory, the essays reveal how the permeable boundaries between nature and culture, the female body and technology are being crossed in the work of women artists.
Keywords: 1900-1999; approches et analyses; art contemporain; artistes féministes; arts; corps; cours; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Split Britches: Lesbian practice / feminist performance - Case, Sue-Ellen (Routledge, 1996)
La compagnie de théâtre Split Britches a ouvert la voie en matière de performances lesbiennes innovantes et stimulantes au cours de la dernière décennie. Split Britches: Lesbian Practice/Feminist Performance est une célébration tant attendue du théâtre et de l'écriture de Lois Weaver, Peggy Shaw et Deborah Margolin, qui composent cette troupe exceptionnelle. Cette anthologie unique est accompagnée de : * sept des textes de performance les plus appréciés de Split Britches * une introduction critique et historique de Sue-Ellen Case * des notes de programme pour accompagner chacune des pièces * une gamme d'illustrations photographiques époustouflantes La publication des textes de la pièce Split Britches, rassemblés ici pour la première fois, offre un accès inestimable à ces célèbres pièces de performance tant pour les étudiant.e.s que pour le public des arts contemporains.
Keywords: amériques; arts; discipline; genre; régions géographiques; théâtre; états-unis

Femmes rebelles : naissance d'un nouveau roman africain au féminin - Cazenave, Odile (L'Harmattan, 1996)
"Femmes rebelles " porte sur la nouvelle génération d'écrivainsfemmes africaines francophones des dix dernières années et l'évolution frappante de leur écriture dans ce court laps de temps. Aux premières oeuvres de témoignage du début des années 80 s'est substituée une deuxième phase montrant une écriture plus agressive, plus revendicatrice : . Ce livre examine le mécanisme de rébellion que les écrivains femmes ont instituées à cet effet dans leur critique de l'Afrique d'aujourd'hui.
Keywords: 1900-1999; 1980-1989; afrique; afro-féminisme; approches et analyses; cours; discipline; fem1000; femmes* noires; féminisme africain; premier cycle; périodes historiques; régions géographiques; thématiques; écriture des femmes*; études littéraires

Heterosexual plots and lesbian narratives - Farwell, Marilyn R. (New York University Press, 1996)
Qu’est-ce que la littérature lesbienne ? Doit-il contenir des personnages ouvertement lesbiens et les présenter sous un jour positif ? L’auteurice doit-iel être ouvertement (ou secrètement) lesbienne ? Doit-il y avoir un thème lesbien et doit-il être politiquement acceptable ? Marilyn Farwell examine ici le travail d'écrivaines tels qu'Adrienne Rich, Marion Zimmer Bradley, Jeanette Winterson, Gloria Naylor et Marilyn Hacker pour répondre à ces questions. Divisant leurs écrits en deux genres : l'histoire romantique et l'histoire héroïque, ou de quête, Farwell aborde certaines des questions les plus problématiques à l'intersection de la littérature, du sexe, du genre et du postmodernisme. Illustrant comment le conflit générationnel entre les lesbiennes-féministes d’il y a vingt ans et les théoricien.nes queer d’aujourd’hui attise les feux critiques de la théorie lesbienne et littéraire contemporaine, Heterosexual plots and lesbian narratives conclut en plaidant en faveur d’une définition large et généreuse de l’écriture lesbienne.
Keywords: amériques; approches et analyses; arts; discipline; europe; lesbianisme; personnes lesbiennes; postmodernisme; royaume-uni; régions géographiques; états-unis; études littéraires

Postcolonial subjects: Francophone women writers - Green, Mary (University of Minnesota Press, 1996)
Sujets postcoloniaux » est un projet collectif centré sur les questions de langue, d'identité et de voix alors qu'ils abordent les questions de genre, de race, d'ethnicité, de culture et de nation. Les essais critiques présentés ici portent sur les contributions littéraires de femmes contemporaines écrivant en français dont les liens culturels, les identités ethniques et les racines historiques se situent au-delà de l'Hexagone, au-delà de la carte à six faces de la France.
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; francophonie; féminisme décolonial; littérature; premier cycle; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires

The art of reflection: women artists'self-portraiture in the twentieth century - Meskimmon, Marsha.. (Columbia University Press, 1996)
Self-portraiture has long been a means for the male artist to assert an identity as masterful creator or tortured soul; women have overwhelmingly been presented as objects, and rarely as subjects of self-portraiture. In recent years, however, women artists have used their work to disrupt this tradition. With 43 illustrations of works by Louise Bourgeois, Frida Kahlo, Alice Neel, Cindy Sherman, and Jo Spence, among others, The Art of Reflection is the first sustained inquiry into the appropriation of self-portraiture by women. In suggestive critical meditations on paintings, photographic work, sculpture, performance art, and body art, Marsha Meskimmon shows how twentieth-century women artists have undermined male-centered definitions of how "the artist" depicts the self. Drawing upon feminist theory and philosophy from Simone de Beauvoir to Luce Irigaray, The Art of Reflection casts doubt on the idea of self-portrait as a mirror, in which the static self is rendered accurately and naturalistically. Meskimmon evokes a series of myths about what an artist is, how "he" should be represented, and how "his" work is to be read as autobiography. Through close readings of the imaginative self-representations of women artists -as male artist and god, as central player in the studio and in the Christian passion- she shatters these myths. In an absorbing assessment of the ways women artists have negotiated the complex group of roles ascribed to "woman," Meskimmon considers the partially nude painting by pregnant artist Paula Modersohn-Becker and performance artist Annie Sprinkle's confrontation of the thin line between celebration of female sexuality and objectification of the female body. As a nuanced appreciation of the interpretations of self-portraiture among women artists, The Art of Reflection will prove an invaluable resource on a subject that has received little attention from art criticism. Meskimmon's work also presents a bold challenge to critical tradition, compelling readers to rethink the meaning of the genre as a whole.
Keywords: 1900-1999; arts; corps; cours; critique d'art; discipline; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; représentation; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

Inside the visible: an elliptical traverse of 20th century art in, of, and from the feminine - Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Mass); Kanaal Art Foundation.; Zegher, M. Catherine de; Institute of Contemporary Art (Boston, Massachusetts); Kanaal Art Foundation. (MIT Press, 1996)
Published on the occasion of a major exhibition opening at the Institute of Contemporary Art in Boston, Inside the Visible presents a gendered reading of more than thirty women artists of vastly different background and experience. The work of important yet previously "invisible" figures is highlighted alongside the work of established artists to create a retheorized interpretation of the art of this century. Structured in terms of recurrent cycles over time, Inside the Visible focuses on three periods (the 1930s and 1940s, the 1960s and 1970s, and the 1990s) that anticipated a wave of political repression, nationalism, and xenophopia, often stimulating artistic production that redefined practice. Illustrated essays document each artist in the collection. In addition, four general essays trace the connections among the artists. These take up such issues as why artistic recognition eluded certain artists and why their work is only just becoming visible today. They also address overlapping themes such as gender and sexuality; the intersection of racial, class, ethnic, sexual, and regional identities; and the nature of the relationship between work and viewer.
Keywords: 1900-1999; 1930-1939; 1940-1949; 1960-1969; 1970-1979; 1990-1999; approches et analyses; artistes féministes; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; queer; thématiques